Spectrum trading and sharing in unmanned aerial vehicles based on distributed blockchain consortium system. (October 2022) - Liu, Lijuan; Shafiq, Muhammad; Sonawane, Vijay R; Murthy, Mantripragada Yaswanth Bhanu; Reddy, Pundru Chandra Shaker; Reddy, K.M.N. Chaitanya kumar
Abstract: Unmanned Aerial Vehicles (UAVs), used primarily for aerial surveying, can monitor control information and carry out stalking tasks connected to the Internet of Things (IoT) using advanced wireless technology. It's limited to short distances where the delicate aerial communication system can share a spectrum with terrestrial systems. Moreover, severe privacy and security concerns are due to the unlicensed broadcasting and wireless UAV transmission networks. Therefore, this paper focus on developing a blockchain-based spectrum trading and sharing system that addresses security concerns and maintains user privacy. Mobile network operators can exchange spectrum without relying on a third party using a Distributed Blockchain Consortium System (DBCS). As a result, data is well-protected from plaintext, stalker, and ciphertext attacks, making it easier to track, manage, and control services. Experimental; results showed that the proposed DBCS outperformed other conventional systems in terms of security and performance. Graphical abstract: Image, graphical abstract